Rancang Bangun Proses Bisnis untuk Digitalisasi Desa Kanrung Kabupaten Sinjai - Rahmi Rahmi; Muh.Amil Siddik; Sampetoding, Eliyah Acantha Manapa; Yulita Sirinti Pongtambing (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Digital Village Index (DVI) and Sustainable Development Goals (SDGs) is a method or technique of measuring the digitalization maturity and maturity of a village through the analysis of relevant indicators that are suitable for the village. Measurement of village digitalization is a very important thing to do in order to evaluate existing digitalization activities and to prepare further digitalization planning. This research aims to analyze digitalization in Kanrung Village, which will show how the readiness, opportunities, and challenges of the village towards a digital village based on the Digital Village Index (DVI) and Sustainable Development Goals (SDGs). The results of this study show that the level of measurement is still at level 2 (Connected), where the village has digital technology, but it has not been implemented and the process of correspondence services is still manual.